The Ability in Using Adjective Clause in Writing Narrative Paragraph at Grade XI Students of SMA Negeri 1 Siantar - evanansi Marpaung (Universitas Kapuas, 2020)
This study is about the ability in using adjective clause in writing narrative paragraph at grade XI students of SMA Negeri 1 Siantar. The problem of this thesis is whether the students are able or not in using adjective clauses in writing narrative paragraph. The writer makes the hypothesis that the students are able in using adjective clauses and the students are unable in using adjective clauses in writing narrative paragraph. The population of this research is made up of grade XI students. The result of the test comes from the students by giving them the test as the instrument. Most of the students are unable in using adjective clauses in writing narrative paragraph. Key Words: Adjective Clause, Narrative Paragraph, Writing, Students